Udokumentowanie sprawozdań finansowych (tezy do dyskusji) - Kwiecień, Mirosława (Documentation of Financial Statements (Theses to Discussion), 2005)
The Author's attempt is to answer following question: whether in Polish economic activity the chart of the accounts is the documentation of Financial statement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 11-14